Economic evaluation of 'Men on the Move', a 'real world' community-based physical activity programme for men. (3rd September 2020) - Kelly, Liam; Harrison, Michael; Richardson, Noel; Carroll, Paula; Egan, Tom; Ormond, Gillian; Robertson, Steve
Abstract: Background: Physical activity (PA) interventions capable of producing health benefits cost effectively are a public health priority across the Western world. 'Men on the Move' (MOM), a community-based PA intervention for men, demonstrated significant health benefits up to 52-weeks (W) post-baseline. This article details the economic evaluation of MOM with a view to determining its cost-effectiveness as a public health intervention to be rolled out nationally in Ireland. Methods: Cost-effectiveness was determined by comparing the costs (direct and indirect) of the programme to its benefits, which were captured as the impact on quality-adjusted life-years (QALYs). For the benefits, cost–utility analysis was conducted by retrospectively adapting various health-related measures of participants to generate health states using Brazier et al.'s (2002) short form-6D algorithm. This in turn allowed for 'utility measures' to be generated, from which QALYs were derived. Results: Findings show MOM to be cost-effective in supporting an 'at risk' cohort of men achieves significant improvements in aerobic fitness, weight loss and waist reduction. The total cost per participant (€125.82 for each of the 501 intervention participants), the QALYs gained (11.98 post-12-W intervention, or 5.3% health improvement per participant) and estimated QALYs ratio costs of €3723 represents a cost-effective improvement when compared to known QALY guidelines. Conclusions: The analysis shows that the cost per QALY achieved by MOM is significantly less than the existing benchmarks of £20 000 and €45 000 in the UK and Ireland respectively, demonstrating MOM to be cost-effective.